Education Management of Republic Indonesia Defense University Towards World Class Defense University - Zainal Muhtar; Yosal Iriantara; Sri Handayani (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
Republic Indonesia Defense University (RIDU) was established by The Minister of Education Letter Number: 29/MPN/OT/2009 dated March 6, 2009 concerning the Establishment of a Defense University and inaugurated by President Susilo Bambang Yudhoyono on March 11, 2009. RIDU develops defense science to meet the needs of the National Defense System. This research discusses the educational management RIDU towards the world class defense university based on Planning, Organization, Actuating, and Controlling (POAC). The method used is a descriptive qualitative method. The results showed that RIDU has moved forward towards the World Class Defense University.